Konsep Hotel Syariah Dalam Perspektif Fiqh Islam Kontemporer - Asyifa Alibia; Hadiat (STAI Al-Mas'udiyah, 2022)
The concept of a sharia hotel has developed into a trend in the hospitality business today, in big cities there have been many sharia hotels. The purpose of this research is to analyze the concept of sharia hotel in contemporary fiqh perspective. The research method used is library research. Data were collected through observation and documentation, then analyzed by qualitative analysis. The results of the study show that the criteria for the sharia hotel concept that are suitable for use are in accordance with the rules, namely: Syiar and Appearance, Facilities, Worship and Da'wah, Managerial and Finance. The concept of a shari'ah hotel is in line with the times or contemporary, adapting to the rules based on the Qur'an. adapted to current conditions.